High loading of pd nanoparticles by interior functionalization of mofs for heterogeneous catalysis - Gole, Bappaditya; Sanyal, Udishnu; Banerjee, Rahul; Mukherjee, Partha Sarathi (Inorganic Chemistry, 2016)
In this report, the issue related to nanoparticle (NP) agglomeration upon increasing their loading amount into metal-organic frameworks (MOFs) has been addressed by functionalization of MOFs with alkyne groups. The alkynophilicity of the Pd2+ (or other noble metals) ions has been utilized successfully for significant loading of Pd NPs into alkyne functionalized MOFs. It has been shown here that the size and loading amount of Pd NPs are highly dependent on the surface area and pore width of the MOFs. The loading amount of Pd NPs was increased monotonically without altering their size distribution on a particular MOF. Importantly, the distinct role of alkyne groups for Pe(2+) stabilization has also been demonstrated by performing a control experiment considering a MOF without an alkyne moiety. The preparation of NPs involved two distinct steps viz. adsorption of metal ions inside MOFs and reduction of metal ions. Both of these steps were monitored by microscopic techniques. This report also demonstrates the applicability of Pd@MOF NPs as extremely efficient heterogeneous catalysts for Heck-coupling and hydrogenation reactions of aryl bromides or iodides and alkenes, respectively.